Mnogoplodne nosečnosti po postopkih neposrednega vnosa semenčice v citoplazmo jajčne celice (ICSI) - Zorn, Branko (Zdravniški vestnik, 2003)
Background. Because of complicattons related to multiple pregnancies after in vitro fertilization this pathology represent a real problem. Intracytoplasmic sperm injection (ICSI) may lead to higher risk in developing monozygotic pregnancies. We sought to investigate whether the multiple pregnancies after ICSI differ of those consecutive to classical in vitro fertilization (IVF) andif counseling for transfering one or at most two embryos is efficient in preventing multiple pregnancies. Methods. We analyzed retrospectively data concerning the incidence of multiple pregnancies before and after the transferof limited number of embryos. Results. In transfering two cleaving stage embryos (day 2) or blastocysts (day 5), when pregnancy rate is high, theincidence of multiple pregnancies is 25 and 17%. After transfer of one blastocyst the highest the pregnancy rate and the lowest the incidence of multiple pregnancies. Conclusions. The best way to avoid multiple pregnancies consist in transferring one or at most two embryos. The monozygotic twin pregnancy we observed was consecutive to the transfer of frozen-thawed blastocyst.
Keywords: Embryo Transfer; fertilization; Fertilization In Vitro; human pregnancy; in vitro fertilization; Nosečnost; Nosečnost večplodna; Nosečnost, izid; oploditev; Oploditev in vitro; Pregnancy; Pregnancy Outcome; Pregnancy, Multiple; Spermatozoa; Spermiji; umetna oploditev; večplodna nosečnost; zapleti; Zarodek, prenos